Artificial intelligence in oral medicine - Qawasmeh, Nour; Serriya, Mahran Abu; Muhamad, Abu-Hussein (Journal of Neonatal Surgery, 2025)
Artificial intelligence (AI) is a technology which is quickly advancing and has captivated the minds of researchers across the globe. The adoption of artificial intelligence (AI) in healthcare is developing while profoundly changing the face of healthcare delivery. There is a marked increase in the evolution of AI from the last decade, which has been showing tremendous improvement and dentistry is no exception. AI has its importance in dentistry, especially in oral medicine , which includes patient diagnosis, storage of patient data, and the assessment of radiographic information which will provide improved healthcare for patients. Regardless of many improvements and advances, AI is still in its teething stage, but its potential is boundless. This technology is tremendously utilized for easy and early diagnosis, proper treatment of lesions of oral cavity, advanced breakthroughs in image recognition techniques, of suspicious premalignant, and malignant changes of oral cavity with satisfying outcome. A thorough knowledge regarding the adaptation of technology will not only help in better and precise patient care but also reducing the work burden of the clinician